The prevalence of Diabetic Retinopathy in a Tertiary Centre in Western Region, Nepal - Pun, Chandra Bahadur; Tuladhar, Sarita; Upadhyaya, Tirtha Lal; Gurung, Jamuna; Dhungana, Durga (Journal of Gandaki Medical College-Nepal, 2020)
Background: Diabetes mellitus is a multisystem disease. It has multiple complications like retinopathy, neuropathy, nephropathy, diabetes ketoacidosis, and stroke. Diabetes retinopathy (DR) is one of the blinding complications of diabetes. This study was done to find out the prevalence of diabetic retinopathy among diabetic patients attending in the outpatient department (OPD) of internal medicine, Gandaki Medical College and Teaching Hospital (GMCTHRC), Pokhara, Nepal.Materials and Methods: A hospital based cross-sectional study was performed among the 200 diabetes mellitus patients attending in the medicine OPD from 15th December 2017 to 15thDecember 2018. They were referred to eye OPD of GMC. The detailed eye examination including fundus evaluation under mydriasis was done to all the patients. The diagnosis of DR was graded using the Early Treatment Diabetic Retinopathy Study classification (ETDRS). Patients having hypertension and other retinal diseases were excluded from the study. Data analysis was done using statistical package for social sciences (SPPS) version 11.20.Results: The mean age of the patients was 63.02 ±11.8 years. In our study 60.5% of the patients were male and 39.5% were female. Diabetes retinopathy was seen in 29.5% patients, of which non proliferative diabetes retinopathy (NPDR) was present in 19.5%, proliferative diabetes retinopathy (PDR) in 9.5% and 0.5% had diabetes maculopathy.Conclusion: The prevalence of DR is quite significant in the people with diabetes. Early diagnosis and management of retinopathy will help to avoid blindness due to the diabetic retinopathy.